Pengaruh Profitabilitas Dan Leverage Terhadap Pengurangan Pajak (Penelitian Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Diah Andari; Nadila Andriana; Citra Mariana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The Indonesian government is increasingly optimizing tax revenues as a source of income. The implementation of tax collection by the government does not always receive a good response from companies or agencies. The government pays quite a lot of attention to taxes so the government expects tax payments to be as high as possible to finance government programs. However, unlike companies, taxes describe costs or burdens that will reduce a company's net profit, so companies will pay taxes as low as possible. This research aims to know whether profitability and leverage influence tax avoidance in mining sector companies listed on the Indonesia Stock Exchange in 2018-2022. The factors tested in this research are profitability and leverage as the independent variable, while tax avoidance as the dependent variable. The research method used in this research is descriptive and verification. The population in this research is mining sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique used in this research is non-probability sampling with a purposive sampling method. The data analysis used in this research is multiple regression analysis using Eviews 12. The results show that partially and simultaneously, profitability and leverage do not affect tax avoidance. The research results also show that the value of profitability and leverage influencing tax avoidance is 6.51%, and the remaining 93.49% influenced by other variables outside the research. Keywords: profitability, leverage, tax avoidance